Effect of in-situ formed oxide and carbide phases on microstructure and corrosion behavior of Zr/Y doped CoCrFeNi high entropy alloys prepared by mechanical alloying and spark plasma sintering - Kotan, Hasan; Tekin, Mustafa; Bayatli, Aleyna; Bayrak, Kuebra Gurcan; Kocabas, Mustafa; Ayas, Erhan (Elsevier Sci Ltd, 2023)
The present work has examined the microstructural evolution, thermal stability, hardness, and corrosion behavior of Zr/Y doped CoCrFeNi HEAs prepared through high-energy mechanical alloying followed by spark plasma sintering (SPS) at 1100 degrees C. The achieved microstructures were investigated by XRD and TEM techniques. The results showed that investigated HEAs consist of an fcc solid solution of CoCrFeNi matrix with in-situ formed Cr-C carbides and Cr/Zr/Y based oxide phases. The SPS processing of CoCrFeNi yielded grain growth to 370 & PLUSMN; 60 nm, while 240 & PLUSMN; 160 nm grain size with bimodal grain size distribution and 165 & PLUSMN; 38 nm grain size were achieved with Zr and Y additions, respectively. The effects of microstructural changes on the hardness and corrosion behaviors of HEAs were also investigated. Compared with 372 & PLUSMN; 15 HV hardness of CoCrFeNi HEA, 445 & PLUSMN; 26 HV and 563 & PLUSMN; 58 HV hardness values were determined with Zr and Y doped HEAs, respectively. The increase in hardness is mainly ascribed to the precipitation strengthening of carbide and oxide phases as well as smaller grain sizes. The corrosion analysis showed that, although the achieved smaller grain sizes and the presence of different oxide types when dopped with Y and Zr impaired the corrosion resistance, the investigated HEAs have reasonable resistance to corrosion when compared to SS304 stainless steel.
Keywords: High entropy alloys; Mechanical alloying and milling; Alloy design; Microstructure; Grain growth; Oxidation